Hormonal analysis provides new insights on reproductive features in Antarctic notothenioids: a trial in Lepidonotothen - Novillo Estofan, Julio Manuel; Elisio, Mariano; Moreira, María Eugenia; Macchi, Gustavo Javier; Barrera Oro, Esteban
The knowledge of reproductive biology in notothenioids arises exclusively frommacroscopic and histologic descriptions, without the complement of hormonal analysis.Our study provides for first time in Lepidonotothen nudifrons adult females, informationon oocyte growth and change in testosterone and estradiol plasma levels throughout theovarian growth. Sampling included near 100 specimens caught at Potter Cove (PC), SouthShetland Islands (SSI), from November to late March of 2016-2018. Histological analysisconfirmed the macroscopic characteristic of two distinct cohorts of oocytes: one leadingclutch (Lc) of large orange vitellogenic oocytes, to be spawned in the upcomingreproductive season, and a second clutch of smaller whitish previtellogenic oocytes. InMarch, females (n=17) attained gonado-somatic index of 13-20% (16.73±4.20), totalfecundity of 2196-4652 oocytes/female (3209±740) and Lc oocytes of 1.7-2.1 mm. The Lcoocytes growth was significantly associated with photoperiod, with no diameter variationuntil the summer solstice, when they began to grow linearly with an estimated rate of0.01 mm/day. Testosterone and estradiol increased together with the oocyte growingthroughout the analyzed seasons, with a higher rise rate during March. The significantplasma level increase of both sex steroids observed in March and the reproductive effort data suggest that: (1) specimens were at a late vitellogenesis stage just prior to theoocyte final maturation in March, and thus L. nudifrons spawning period might onsetfrom this month at SSI; (2) PC is likely a spawning site for L. nudifrons, which reinforce thehypothesis that nearshore areas are spawning grounds for some notothenioids. Fil: Novillo Estofan, Julio Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico ...